T cell protein tyrosine phosphatase prevents STAT1 induction of claudin‐2 expression in intestinal epithelial cells. Issue 1 (14th August 2017) - Krishnan, Moorthy; McCole, Declan F.
Abstract: T cell protein tyrosine phosphatase (TCPTP) dephosphorylates a number of substrates, including JAK–STAT (signal transducer and activator of transcription) signaling proteins, which are activated by interferon (IFN)‐γ, a major proinflammatory cytokine involved in conditions such as inflammatory bowel disease. A critical function of the intestinal epithelium is formation of a selective barrier to luminal contents. The structural units of the epithelium that regulate barrier function are the tight junctions (TJs), and the protein composition of the TJ determines the tightness of the barrier. Claudin‐2 is a TJ protein that increases permeability to cations and reduces transepithelial electrical resistance (TER). We previously showed that transient knockdown (KD) of TCPTP permits increased expression of claudin‐2 by IFN‐γ. Here, we demonstrate that the decreased TER in TCPTP‐deficient epithelial cells is alleviated by STAT1 KD. Moreover, increased claudin‐2 in TCPTP‐deficient cells requires enhanced STAT1 activation and STAT1 binding to the CLDN2 promoter. We also show that mutation of this STAT‐binding site prevents elevated CLDN2 promoter activity in TCPTP‐deficient epithelial cells. In summary, we demonstrate that TCPTP protects the intestinal epithelial barrier by restricting STAT‐induced claudin‐2 expression. This is a potential mechanism by which loss‐of‐function mutations in the gene encoding TCPTP may contribute to barrier defects in chronic intestinal inflammatory disease.